MELACAK ALGORITMA HISAB AWAL BULAN QAMARIYAH DALAM KITAB NURUL ANWAR - Ahmad Fauzan (IAIN Pekalongan, 2014)
This research examines the Risalah al-Falak Nurul Anwar min Muntaha al-Aqwal fi Maâ€™rifah Hisab al-Sinin wa al-Hilal wa al-Khusuf ala HaqÄ«qÄ« bi al-TahqÄ«q bi Rasd al-Jadid, the work of KH. Nur Ahmad, SS, using content analysis. The results are: First, the book calculations algorithm in terms of determining the beginning of the month Qamariyah fall under hisab Haqiqi bi al-TahqÄ«q. While Spherical Trigonometry is the basis for its theory and calculation. Second, in the making process, the book used BadÄ«â€™ah al-MitsÄl and al-KhulÄsah al-WÄfiah as reference. This literature research also found that the trend of the data is taken from the book of BadÄ«â€™ah al-MitsÄl, while the calculation is taken from the book of al-KhulÄsah al-WÄfiah, by adapting the rules of modern astronomy.